Liver Abscess after Common Hepatic Artery Embolization for Delayed Hemorrhage Following Pancreaticoduodenectomy: Case Report - Yuichi Sanada; Hiroki Kondo; Satoshi Goshima; Masayuki Kanematsu; Yoshihiro Tanaka; Yasuharu Tokuyama; Shinji Osada; Kazuhiro Yoshida (Case Reports in Medicine)
A 55-year-old man underwent pancreaticoduodenectomy for bile duct carcinoma in March 2009. The patient developed anastomotic leakage and had a short episode of hemorrhage from the drainage tubes with spontaneous disappearance. CT and upper endoscopy did not reveal the source of bleeding. A massive life-threatening hemorrhage occurred on the 18th postsurgical day. Emergency angiography showed a 2.7-cm pseudoaneurysm of the gastroduodenal artery stump, and hepatic artery embolization was performed. After embolization, an abscess appeared in segments 2/3 of the liver without involving the right lobe. We treated conservatively by drainage and antibiotics. During the course of therapy after embolization, the patient experienced several episodes of high fever but did not develop hepatic failure. On the 68th day after embolization, the abscess had penetrated to the lesser sac, which was immediately treated by percutaneous drainage. Anastomotic leakage was treated by continuous irrigation from the drain, for which complete resolution was achieved by the 34th day after embolization. The patient was discharged 101 days after embolization. Imaging and the clinical course demonstrate a unique mechanism of abscess formation after embolization.